A reform option for pension fund contribution as tax expenditure in South Africa: A microsimulation model approach using tax administrative data - Ada Jansen; Winile Ngobeni; Wynnona Steyn (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
South Africa has a progressive broad-based personal income tax system with relatively few tax expenditures. The two most important are the medical contribution plus additional tax credits for medical expenses, and the deductions allowed for retirement contributions. A pertinent question for tax reform in South Africa is whether redistributive gains can be achieved by restructuring expenditures in the personal income tax system. This paper considers the redistributive implications of converting the tax deduction for retirement contributions to a tax credit. This would build on the gains achieved by introducing a medical tax credit system in 2012. We analyse the tax revenue gains/losses of income groups and in total in terms of distributional effects and progressivity outcomes using a static microsimulation model based on data for the 2019/20 tax year. We find a high concentration of taxpayers in terms of taxable income and retirement contributions. The concentration of contributions is highly skewed towards lower- and middle-income earners, whose annual contribution amounts are low compared with higherincome earners. We recommend a conversion rate that considers the current distribution of taxpayers contributing to retirement funds. Converting the pension contribution deduction to a tax credit would raise additional revenue and make the tax system more progressive, benefiting low-income earners with marginal tax rates of less than the proposed conversion rate. The revenue gained would provide increased fiscal space to fund social expenditure or reduce government debt. Further distributional and behavioural analyses are needed on low-income earners and those earning below/above the minimum tax threshold, to refine understanding of the impact on lowand middle-income earners' contributions to retirement funds.
Keywords: H23; H24; 330; retirement fund contribution; tax expenditure; microsimulation; tax credit